Plant Functional Niches in Forests Across Four Climatic Zones: Exploring the Periodic Table of Niches Based on Plant Functional Traits - Yu, Ruoyun; Huang, Jihong; Xu, Yue; Ding, Yi; Zang, Runguo (Frontiers in Plant Science, 2020)
Previous studies have indicated that a niche variation scheme, similar to the periodic table of elements, can be constructed based on functional traits. The periodic table of niches for species is defined as a multidimensional ordination scheme of niche relationships and their orders in a specific biotic community. Comparing functional trait-based niches is extremely useful in theoretical studies of plant ecological strategies, community assembly, and the geographic differentiation of biomes across different climatic zones. Here, data for 11 functional traits belonging to three fundamental niche dimensions (leaf economy, mechanical support, and reproductive phenology) were compiled for 215 woody species from forests across four climatic zones (tropical, subtropical, warm-temperate, and cold-temperate). We constructed the periodic table of niches based on the functional traits of plants in different communities and explored their variations among biomes. A principal component analysis (PCA) was performed to derive the dominant gradients of trait combinations for each individual niche dimensional dataset. Then species scores for the first two axes (PC1 and PC2) were used as inputs for a second PCA to ordinate species in the continuous niche space constrained by the three niche dimensions. Changes in the functional niches of plants from the four biomes along the PC1 and PC2 of niche space were examined based on species scores. Leaf economy was the dominant functional dimension in the plant niche space, followed by mechanical support. Considerable niche convergences among different species were found in the niche space for each biome, except cold-temperate forest. The species niches varied mainly with the increasing specific leaf area/decreasing stem tissue density along PC1, and with the decrease of leaf area/plant size along PC2 from tropical to temperate forests, suggesting that the ecological strategies of plants in the four biomes changed from conservative to acquisitive with an increase in latitude. Our results confirmed that the periodic table of niches does exist and can be constructed by major functional dimensions composed of dominant functional traits. The periodic table of niches effectively reflects the changes of ecological strategies of plant species in biomes across different climatic zones.